Case Report: Early detection and intervention of congenital portosystemic shunts in children - Zhang, Ying; Yu, Tianzhuo; Mi, Yanhong; Zhang, Wenzhi; Yang, Gaoyi (Frontiers in Oncology, 2023)
Abstract Congenital portosystemic shunts (CPSS) are rare vascular anomalies that cause abnormal communications between the portal and systemic venous systems and may be incidentally detected on imaging or via abnormal laboratory parameters due to the lack of specificity in the condition’s clinical presentation. Ultrasound (US) is a common tool for examining abdominal solid organs and vessels and is the initial imaging modality for diagnosing CPSS. Here we report the case of an 8-year-old Chinese boy with CPSS diagnosed using color Doppler US. Doppler US first found intrahepatic tumor, then revealed that the left portal vein was directly communicating with the inferior vena cava, and the boy was finally diagnosed with intrahepatic portosystemic shunts. Interventional therapy was employed to occlude the shunt. During the follow-up, the intrahepatic tumor disappeared and no complications. Hence, to be able to differentiate such vascular anomalies, clinicians should be fairly acquainted with the normal ultrasonographic anatomical features in daily clinical work. Furthermore, increased disease awareness and advances in imaging equipment and technology are essential for CPSS diagnosis.